THE ROLE OF ARTIFICIAL INTELLIGENCE IN GENERAL PRACTICE - CHALLENGES AND POTENTIAL RISKS - Stankov, Suncica (Medicinski časopis, 2025)
Artificial intelligence has a significant role in the field of primary health care and its application is becoming more common. Artificial intelligence helps doctors of general medicine on several levels, in high-quality diagnosis and therapy planning, and by processing a large amount of data, in providing more time for the implementation of sophisticated tasks. Despite its many advantages, it is believed that artificial intelligence can negatively affect the doctor-patient relationship. Artificial intelligence in general medicine represents a significant component in the further development of personalized medicine, individual approaches to treatment and quality health care for patients.